DISTRIBUTION OF INHERITANCE TO ADOPTED CHILDREN ACCORDING TO BATAK TOBA CUSTOMARY LAW - Verawaty, Lenny; Nadirah, Ida (NOMOI Law Review, 2025)
Adoption of children has become a societal need and is part of the family law system, because it concerns the interests of each person in the family. One of the legal consequences of adoption is regarding the status of the adopted child as the heir of his adoptive parents. This status regarding adopted children often causes problems in the family. Problems that can arise are regarding whether or not the adoption of a child is valid, as well as the position of the adopted child as the heir of the adoptive parents. The research method used is Normative Legal Research (Normative Jurisdiction), namely a legal research method that uses secondary data sources, by examining related library materials. The adoption of a child in the Batak Toba traditional community is carried out by means of a traditional ceremony (eating together) which is attended by the dalihan natolu, traditional king, dongan sahuta and other families. So the position of the adopted child regarding the division of the adoptive parents' inheritance is valid according to customary law, and there are also some communities who continue to ratify and determine the child's adoption with a court decision, after a traditional ceremony. Then it is registered at the local civil registration office, so that the adopted child's name is listed as a family member on his parents' family card. And in terms of inheritance distribution, adopted children have the same position as biological children.